Response evaluation of the neck in oropharyngeal cancer: Value of magnetic resonance imaging and influence of p16 in selecting patients for post-radiotherapy neck dissection. (21st October 2015) - Lilja-Fischer, Jacob K.; Jensen, Kenneth; Eskildsen, Helle W.; Fink-Jensen, Vibeke; Nielsen, Viveque E.
ABSTRACT: Background. Residual neck disease after radiotherapy in advanced oropharyngeal squamous cell carcinoma (OPSCC) is associated with increased mortality, and some patients may benefit from post-radiotherapy neck dissection (PRND). The aim of the present study was to assess the value of magnetic resonance imaging (MRI) and other clinical characteristics in selecting patients for PRND. Materials and methods. Retrospective cohort study. Consecutive patients with N+ OPSCC were included. Medical records, pathology reports and imaging reports were reviewed. Pre- and post-therapeutic imaging was re-evaluated. Results. A total of 100 consecutive patients from a three-year period were included. Neck response was evaluated with MRI two months after treatment. Sixty patients were suspicious for residual neck disease, and were offered surgery; seven of these patients had histologic evidence of carcinoma. Cumulative neck failure after three years was 14% (8.4–24%), and did not differ significantly among patients with positive compared to negative MRI (radiologist's initial description; p = 0.47, log-rank test). Applying neck failure as gold standard, sensitivity and specificity of MRI was 69% and 41%, respectively; positive and negative predictive value was 15% and 90%. Patients with p16 + disease had significantly larger lymph nodes after treatment, and imaging based on lymph node size resulted in many false positives. Analysis of receiver operating characteristic curves in 191 individual lymph nodes showed that a short axis ≥ 10 mm should be classified as suspicious. Furthermore, T-stage and p16-status were associated with increased risk of neck recurrence. Salvage was successful in four patients with early detected nodal recurrence. Conclusion. These results suggest that lymph node size, T-stage and p16 status could be used in selecting patients for PRND in OPSCC. Yet, early anatomical imaging may be inappropriate for evaluating neck response in patients with p16 + disease as enlarged lymph nodes often do not indicate residual neck disease.